Development of a Mobile Menu Book as a Media For Learning Food Service in Tourism Schools - Aditia Gustiana; Cica Yulia; Quienera Joshua (Universitas Ahmad Dahlan, 2023)
The important to remember that technological progress is unpredictable, and the landscape of immersive and interactive systems may have seen significant progress. Developers and innovators are constantly exploring and experimenting with new possibilities, making the future of immersive technology exciting and full of potential as a means to improve education. The research seems to adopt a mixed-methods approach, utilizing both qualitative methods for needs analysis and design stages, and quantitative methods for testing the product's effectiveness. By involving both teachers and students in the development process, the application can better meet their specific needs and preferences. The validation data collected from the assessment by validators suggests that the application has been well-received and is considered valid for use in food service learning. With an average percentage of 85.25% in the valid category, it implies that the application meets the required standards and requirements for an effective learning tool. Overall, the Android-based learning media application holds the potential to contribute significantly to the field of education, particularly in cooking learning. As technology continues to advance, similar applications tailored to other industries and fields of study can also play a crucial role in addressing the increasing demand for skilled human resources in various industries.